2020
DOI: 10.4085/1062-6050-85-19
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Collegiate Athletic Trainers, Part II: Treating Concussed Student-Athletes

Abstract: Context Conflict between athletic trainers (ATs) and other stakeholders can occur because of competing interests over medical decisions regarding concussion. However, we are unaware of any studies specifically exploring these situations across various collegiate athletic affiliations. Objective To investigate the challenges faced by ATs when treating concussed student-athletes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Medical care decisions, especially regarding a studentathlete's readiness to return to play, are often the impetus for conflict between coaches and ATs. 1,2,4,5 Our findings, in conjunction with other literature, 4,5 showed that coaches were eager for their student-athletes to return from injury as soon as possible; however, for ATs in the collegiate setting, the eagerness was viewed at times as pressure. Our participants considered this was an inherent part of their job and expected it from coaches whose goals were successful programs.…”
Section: External Pressures Encountered During Medical Decision Makingsupporting
confidence: 68%
See 3 more Smart Citations
“…Medical care decisions, especially regarding a studentathlete's readiness to return to play, are often the impetus for conflict between coaches and ATs. 1,2,4,5 Our findings, in conjunction with other literature, 4,5 showed that coaches were eager for their student-athletes to return from injury as soon as possible; however, for ATs in the collegiate setting, the eagerness was viewed at times as pressure. Our participants considered this was an inherent part of their job and expected it from coaches whose goals were successful programs.…”
Section: External Pressures Encountered During Medical Decision Makingsupporting
confidence: 68%
“…Our primary focus was to explore the ATs' experiences regarding medical care decision making, particularly as it pertains to return to play. Growing evidence 1,2,4,5 has indicated that ATs face pressure from coaches and other athletic administrators to return athletes to play, possibly before they are ready. Recognizing that ATs face such pressure, we also sought to better understand how ATs cope with these situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conflict between medical and nonmedical personnel in athletic environments is not novel and often manifests as pressure to prematurely return an athlete to play. 2,3 Anecdotal 3-5 and empirical 2,[6][7][8][9] evidence has highlighted this concern for years.…”
mentioning
confidence: 99%